Territories of Contributory Learning (Glocalism: Journal of Culture, Politics and Innovation, 2022)
Places are just as crucial as organisations in the fabric of social life: despite all the homogenising tendencies, the social space, sculpted by the stories that constitute it, continues to prove multiform and rich in diversity. At the end of the 20th century, the radical spatial and temporal reorganisation produced by globalised technical infrastructure redesigned the map of the planet. Now, the pandemic is giving a new direction to spatial and temporal restructuring processes. The outcome is still open, but the processes have their inertial force, destined to characterize the times to come. The direction that will be followed is still largely undetermined because the models that inspire the paths of transformation are vastly different. This paper examines the idea of contributory territories as one possible outcome.
Keywords: territories; contributory learning; globalization; localization; care